Effects of a Chinese-style DASH Diet on Nutritional Health in Hypertensive Patients with Type 2 Diabetes - MU Lisha, GONG Tao, XU Huini, CHEN Dan, TANG Jie, CAI Shuwen, MU Lihong (Zhongguo quanke yixue, 2022)
Background High blood pressure can cause damages of target organs such as the heart, brain, kidneys and retina, while diabetes can cause a series of metabolic disorders, resulting in a variety of complications. Both are major risk factors for cardiovascular and cerebrovascular diseases. Eating a healthy diet may significantly contribute to the prevention and control of hypertension and diabetes. Objective To investigate the effects of a Chinese-style DASH diet in improving the nutritional status of community-living patients with type 2 diabetes and hypertension. Methods Sixty-one hypertensive patients with type 2 diabetes with medical records created in Chongqing Sihai Community Health Center were selected to undergo an eight-week Chinese-style DASH diet intervention, including dietary guidance (at 1 and 2 weeks) , eating the Chinese-style DASH diet provided using a group-based approach (at 3 and 4 weeks) , and home-based medical care (at 5 to 8 weeks) . Food frequency survey and 24-hour dietary recall were used to investigate the dietary structure and nutritional intake at baseline and after intervention. Anthropometric indicators (BMI and waist-to-hip ratio) , blood lipids (triacylglycerol, total cholesterol, high-density lipoprotein cholesterol, low-density lipoprotein cholesterol) , glycemic control and hypertension control status at baseline and after intervention were compared. Results A total of 59 cases were included in the study. Regarding dietary structure after intervention, the average daily intake of soy, nuts, pickled products, fried foods and salt significantly decreased in subjects, while that of fresh fruit, milk and dairy products increased significantly (P<0.05) . Regarding nutritional status, the daily average intake of fat and sodium was significantly reduced, while that of dietary fiber, calcium, potassium and magnesium was significantly increased (P<0.05) . The number of participants eating a diet with a recommended ratio of fat increased significantly (P<0.05) . Health monitoring showed that total cholesterol, low-density lipoprotein cholesterol, systolic blood pressure, diastolic blood pressure and 2-hour postprandial glucose were partially improved after intervention (P<0.05) . From the 4th week of the intervention, the control rate of 2-hour postprandial glucose at follow-up was significantly higher than the baseline level (P<0.05) , and it reached 69.5% at the end of the intervention. Except for the 2nd week of the intervention, the blood pressure control rate at follow-up was notably higher than the baseline level (P<0.05) , and it reached 67.8% at the end of the intervention. Conclusion Eating the Chinese-style DASH diet helps to promote the health in community-living hypertension patients with type 2 diabetes via effectively adjusting the inappropriate diet structure and improving the nutritional status.